PERSPEKTIF LINGKUNGAN DALAM PENGELOLAAN PETERNAKAN - Adi Ratriyanto; Muh Aris Marfai (Universitas Sebelas Maret, 2010)
Animal wastes present in the form of manure, urine, feed, hatchery by product, blood, feather, bone, horn, and rumen material. Unmanaged animal waste contributes to environment problems. Animal wastes consist of nitrogen, phosphate, pathogen and organic material. Over absorption of nitrogen affect to melkomoglobinemia, meanwhile eutrophication happened due to over phosphate on the water bodies. Pathogen cause infection and diseases, and furthermore less oxygen due to over organic material in water decreasing fish population. Applying feed enzyme may increase availability of nutrition, performance, and decrease pollution impact due to manure. Well-management of livestock take consideration of environmental aspects, such as awareness of environment risk, balancing nutrition content of the waste animal, waste management, neighbor awarness, understand and obeying the regulation, and consider to the physical factors and applying land evaluation for livestock-site selection. This article responds to the impact of livestock on the environment and discusses factors related to environmental friendly of livestock management.